2020
DOI: 10.1007/s00109-020-01966-z
|View full text |Cite
|
Sign up to set email alerts
|

Need for a precise molecular diagnosis in Beckwith-Wiedemann and Silver-Russell syndrome: what has to be considered and why it is important

Abstract: Molecular diagnostic testing of the 11p15.5-associated imprinting disorders Silver-Russell and Beckwith-Wiedemann syndrome (SRS, BWS) is challenging due to the broad spectrum of molecular defects and their mosaic occurrence. Additionally, the decision on the molecular testing algorithm is hindered by their clinical heterogeneity. However, the precise identification of the type of defect is often a prerequisite for the clinical management and genetic counselling. Four major molecular alterations (epimutations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In our study, the frequency of MLID was 3.4% in the patients with various IDs, and 4.5% in patients with various IDs classified into the SRS-compatible group. Recently, Eggermann et al reported that the frequency of MLID was 3.6% in SRS patients with aberrant findings ( 39 ). These findings suggest that MLID in patients with SRS is less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the frequency of MLID was 3.4% in the patients with various IDs, and 4.5% in patients with various IDs classified into the SRS-compatible group. Recently, Eggermann et al reported that the frequency of MLID was 3.6% in SRS patients with aberrant findings ( 39 ). These findings suggest that MLID in patients with SRS is less frequent.…”
Section: Discussionmentioning
confidence: 99%
“…MLID is not restricted to BWS, since it has been reported in other genomic imprinting diseases [ 22 ]. In BWS, MLID frequency is observed in 20–50% of patients with IC2 LOM [ 6 , 7 , 8 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], while it is very rare among cases with IC1 GOM [ 33 ]. Recently, genome-wide epigenetic defects, comprising both imprinted and non-imprinted loci, have been identified in patients with clinical diagnosis of BWS not confirmed by molecular testing.…”
Section: Genetic and Epigenetic Alterations In Bwsmentioning
confidence: 99%
“…Due to a lack of specificity of these symptoms, and clinical heterogeneity, SRS is often discussed being a differential diagnosis and is genetically tested in patients with growth retardation. Consequently, the detection rate for the currently known molecular disturbances of SRS is only 10–20% (averaged detection rate in different diagnostic centers (unpublished data, [ 2 ]), whereas in clinically well characterized cohorts of SRS patients it reaches nearly 70%.…”
Section: Introductionmentioning
confidence: 99%